2023
DOI: 10.1021/acscentsci.2c01078
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive Dynamics of Bacterial Proteome as a Proxy of Cell Death

Abstract: Temperature variations have a big impact on bacterial metabolism and death, yet an exhaustive molecular picture of these processes is still missing. For instance, whether thermal death is determined by the deterioration of the whole or a specific part of the proteome is hotly debated. Here, by monitoring the proteome dynamics of E. coli, we clearly show that only a minor fraction of the proteome unfolds at the cell death. First, we prove that the dynamical state of the E. coli proteome is an excellent proxy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 65 publications
(123 reference statements)
6
14
0
Order By: Relevance
“…In Figure 6A, we report the data from the previous simulation of the same model but based on the earlier version of OPEP and using the 1.8/2.1 scaling factor. 34 The computed diffusion coefficients already show a good agreement with the model 42 derived from experimental data; see the solid line in Figure 6A. In Figure 6B, we report the results obtained with OPEPv7, which also works very well, reproducing the experimental trend.…”
Section: ■ Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…In Figure 6A, we report the data from the previous simulation of the same model but based on the earlier version of OPEP and using the 1.8/2.1 scaling factor. 34 The computed diffusion coefficients already show a good agreement with the model 42 derived from experimental data; see the solid line in Figure 6A. In Figure 6B, we report the results obtained with OPEPv7, which also works very well, reproducing the experimental trend.…”
Section: ■ Resultssupporting
confidence: 75%
“…To improve the description of crowded systems with the OPEP force field, we benchmarked its predictions of translational diffusion coefficients in homogeneous solutions of bovine serum albumin (BSA) and binary solutions of chymotrypsin inhibitor 2 (CI2) against neutron-scattering (NS) and nuclear magnetic resonance (NMR) data, respectively, obtained for these solutions. , We found that choosing a smaller empirical scaling factor removed the gelation issue and improved the behavior of the protein solutions. Namely, the 1.8/2.1 scaling was used to model the E. coli cytoplasm, and the recovered diffusivities of the proteins were found in good agreement with the experimental distribution of the diffusion coefficients, as a function of protein molecular mass in E. coli ; see ref . However, when considering our benchmark systems no single scaling factor ensured the perfect agreement with experimental data for all the model systems (see Figures S3 and S4 in the Supporting Information).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations